Multimodal Representations of Lithuanian Brands: The Case of “Džiugas”, “Rūta” and “Pieno žvaigždės” - Juzelėnienė, Saulė; Stvolaitė, Aistė (Respectus Philologicus, 2023)
Figurative representations of brand images have not been thoroughly studied in Lithuanian linguistics. The present research aims to investigate the multimodal metaphors and metonymies explored by the famous Lithuanian corporate brands Džiugas, Rūta and Pieno žvaigždės. The work examines how the multimodal metaphors and metonymies of the brands are cognitively structured from the perspective of illustrations, logos and layout. The interaction of verbal and visual elements in corporate discourse is particularly important when expressed using graphics, logos and layout for the corporate mission statements, descriptions of the brand history and other materials available on their websites. The analysis reveals that the most frequent source domains for brand imaging are PERSON/LIVING ORGANISM, SUCCESS, TRADITIONS and CAUSE FOR EFFECT, PART FOR WHOLE, PRODUCT FOR PRODUCER metonymies, among others. In the case of personification, the brand is defined as an individual who possesses the qualities highly valued in corporate discourse: growth, positivity, adaptability, dynamism and collaboration. These metaphors facilitate a better understanding of the brand and contribute to the formation of a persuasive brand image that resonates with consumers. The analysis of the multimodal manifestations of brand identity in the cases of Džiugas, Rūta and Pieno žvaigždės reveals the intricate interplay of metaphor and metonymy in constructing and conveying meaning across various modes of representation. Each brand’s illustrations, logo and layout incorporate visual elements, typography, and colour palettes that contribute to their unique identities and evoke specific associations.